Epigenetics in Families: Covariance between Mother and Child Methylation Patterns - Van Aswegen, Tanya (Brain Sci, 2021)
Theory and research both point at epigenetic processes affecting both parenting behavior and child functioning. However, little is known about the convergence of mother and child’s epigenetic patterns in families. Therefore, the current study investigated epigenetic covariance in mother–child dyads’ methylation levels regarding four stress-regulation related genes (5HTT, NR3C1, FKBP5, and BDNF). Covariance was tested in a general population sample, consisting of early adolescents (M(age) = 11.63, SD(age) = 2.3) and mothers (N = 160 dyads). Results showed that mother and offspring 5HTT and NR3C1 methylation patterns correlated. Furthermore, when averaged across genes, methylation levels strongly correlated. These findings partially supported that child and parent methylation levels covary. It might be important to consider this covariance to understand maladaptive parent–child relationships.